# college algebra

posted by .

Let f denote an odd function and g an odd function. Decide whether the function h(x)=g(x) f(x) is even or odd.

• college algebra -

h(-x) = f(-x)g(-x)

f(-x) = -f(x)

g(-x) = -g(x) ---->

f(-x)g(-x) = f(x)g(x) = h(x)

So:

h(-x) = h(x)

• college algebra -

g(x)*f(x) is an even function, since both f and g change signs when x is replaced by -x

## Similar Questions

1. ### odd and even functions

Using f is odd if f(-x) = -f(x) or even if f(-x) = f(x) for all real x, how do I 1)show that a polynomial P(x) that contains only odd powers of x is an odd function 2)show that if a polynomial P(x) contains both odd and even powders …
2. ### ~*~Algebra!*~

How do you use possible symmetry to determine whether the graph is the graph of an even function, an odd function, of a function that is neither even or odd?
3. ### Math

Let f and g be two odd functions. Prove that: a) f + g is an odd function b) g of f is an odd function I am not even sure where to start, any help that can be provided would be appreciated!
4. ### algebra

The function f is even and the function g is odd. Determine whether the function h(x)= f(x)/g(x) is even or, odd or neither.
5. ### Algebra

Let f(x) = 1 – 3x^2. Which of the following is true?
6. ### Algebra

Let f(x) = 1 – 3x^2. Which of the following is true?